PENGARUH RELIABILITY, RESPONSIVENESS, ASSURANCE, EMPATHY DAN TANGIBLES TERHADAP KUALITAS PELAYANAN PUBLIK (STUDI KASUS KANTOR PELAYANAN TERPADU KOTA DUMAI) - Sitorus, Monang (Jurnal Borneo Administrator, 2009)
This paper describes and analysis influence reliability, responsiveness, assurance, empathy dan tangibles to service quality permit  (Case study of Dumai City Office Service). The theory public service  tested out by the writer by Zeithaml, Parasuraman, and  Berry “Delivering Quality Service Balancing Customer Perception and Expectation” (1990). which consists of  five  dimension namely  Reliability, Responsiveness, Assurance, Empathy dan Tangibles (TERRA).  These five  dimension  were applied by the to analysis to service quality permit.  To identity the  five  influence of  dimension, a survey approach was conducted through a proportional sample of 116  head of household (informants). The data were analyzed by using  Path Analysis, in the  program LISREL ( Linear Structural Relation). The value was found out each dimensions as follows;  ( a). influence reliability ( X1) to service quality permit (Y) is 0,74 (strong category); influence responsiveness (X2) to service quality permit  (Y) is 0,59 (medium category ); influence assurance  (X3) to service quality permit  (Y) is  0,34 (low category); and influence empathy (X4) to service quality permit ( Y) is 0,53 ( medium category), influence tangibles (X5) to service quality permit (Y) is 0.41 (low category). The effect ( X1,X2,X3,X4, X5) to Y is  0.59 (medium category).  After determination influence X1,X2,X3,X4, X5 to Y is 34,81%, and the residue is 65,19% influenced  the other dissimilar factor (epsilon) is transparency, and fairness.    Key Word: Reliability, Responsiveness, Assurance, Empathy, Tangibles and Service  Quality.